Human microsaccade cueing modulation in visual- and memory-delay saccade tasks after theta burst transcranial magnetic stimulation over the frontal eye field - Barquero, Cesar (2023)
Microsaccades that occur during periods of fixation are modulated by various cognitive processes and have an impact on visual processing. A network of brain areas is involved in microsaccade generation, including the superior colliculus and frontal eye field (FEF) which are involved in modulating microsaccade rate and direction after the appearance of a visual cue (referred to as microsaccade cueing modulation). Although the neural mechanisms underlying microsaccade cueing modulations have been demonstrated in monkeys, limited research has investigated a causal role of these areas in humans. By applying continuous theta-burst transcranial magnetic stimulation (cTBS) over the right FEF and vertex, we investigated the role of human FEF in modulating microsaccade responses after the appearance of a visual target in a visual- and memory-delay saccade task. After target appearance, microsaccade rate was initially suppressed but then increased in both cTBS conditions. More importantly, in the visual-delay task, microsaccades after target appearance were directed to the ipsilateral side more often with FEF, compared to vertex stimulation. Moreover, microsaccades were directed towards the target location, then to the opposite location of the target in both tasks, with larger effects in the visual-, compared to, memory-delay task. This microsaccade direction modulation was delayed after FEF stimulation in the memory-delay task. Overall, some microsaccade cueing modulations were moderately disrupted after FEF cTBS, suggesting a causal role for involvement of the human FEF in microsaccade generation after presentation of salient stimuli